William W. Cook: Articles from Law Quad Notes about William W. Cook - Leary, Margaret A. (2006)
This collection of articles published from 2002-2004 is the embryo of a biography I hope to complete so that full information about the life and times of William W. Cook (1858- 1930) is accessible. Cook was important to the University of Michigan and its Law School because he gave virtually all of his considerable fortune to the Law School, and was the first individual to give so much.https://repository.law.umich.edu/books/1034/thumbnail.jp